Logistics sprawl in the Brussels metropolitan area: Toward a socio-geographic typology. (October 2020) - Strale, Mathieu
Abstract: Logistics activities are concentrated around cities, for the purpose of accessing and serving these important markets. However, at a more refined level, because of land prices, availability and modern logistics schemes, suburban locations are preferred. This trend, the so-called logistics sprawl, creates land consumption, longer supply chains and jobs shifts. This article analyses the geography of logistics in the Brussels metropolitan area and highlights this suburbanization, notwithstanding the fact that some particularities appear, due to the Brussels, Belgian and European contexts. In a second step, we construct a spatial typology to understand the fine evolution of the Brussels metropolitan logistics space. These results reinforce our knowledge of logistics geography and add a frequently neglected institutional dimension to the extant literature on the subject – wholesale trade activities.